Exploring the Factors Influencing Consumer Decision-making in the social media Era: A Study of the Dynamics and Trends (Revista Galega de Economía)
In the contemporary landscape of consumer decision-making, the advent and proliferation of social media have significantly transformed the traditional paradigms. The accessibility of social platforms has empowered consumers with unprecedented levels of information, connectivity, and influence. This study explored the evolving dynamics of consumer decision-making within the social media era, delving into the intricate interplay of factors such as online reviews, peer recommendations, influencers, and brand engagement. The massive information on social media has empowered consumers to make more informed choices, while simultaneously presenting challenges for businesses to navigate the complexities of online reputation management. As consumers increasingly rely on social networks for product discovery and validation, the role of trust, authenticity, and social proof emerges as pivotal in shaping purchasing behaviours. The present study is conducted to analyse the factors influencing consumer decision making in social media era and found that factors such as obtaining up-to-date information, convenient communication, sharing experiences, and trust significantly contribute to increased engagement in a brand's social media community. Additionally, the impact of social media on product discovery, evaluation, and choice is evident, with users highly influenced by friends' purchases, actively seeking information, and relying on social media for post-purchase experiences.